Euthanasia dalam Pandangan Moral, Kode Etik Kedokteran dan Perspektif Hukum Islam - Zilfania Rahmawati; Ashif Az Zafi (Alhurriyah, 2020)
The practice of euthanasia in medicine has become a topic that raises various discussions when viewed from different points of view. The existence of differences of opinion that arise from the practice of euthanasia is normal because the practice is related to human life. Based on this, this scientific study aims to determine euthanasia from a moral perspective, a medical code of ethics and in the perspective of Islamic law. The process of collecting data from scientific studies was carried out by means of literature research using qualitative descriptive methods in presenting and analyzing the data obtained. The results of the study show how euthanasia practices are in accordance with the medical code of ethics, moral views and how the law is in Islam.Praktik Euthanasia dalam kedokteran menjadi hal yang menimbulkan berbagai perbincangan bila dilihat dari sudut pandang yang berbeda. Adanya perbedaan pendapat yang muncul dari praktik euthanasia merupakan suatu kewajaran karena praktik tersebut berhubungan dengan nyawa manusia. Berdasarkan hal tersebut studi ilmiah ini bertujuan untuk mengetahui euthanasia dalam pandangan moral, kode etik kedokteran dan dalam perspektif hukum Islam. Proses pengumpulan data studi ilmiah ini dilakukan dengan cara penelitian literatur menggunakan metode deskriptif kualitatif dalam penyajian dan anlisis data yang diperoleh. Hasil dari penelitian menunjukkan bagaimana praktik euthanasia yang sesuai kode etik kedokteran, pandangan moral dan bagaimana hukumnya dalam agama Islam.